If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -15)(2x + 3) = 0 Reorder the terms: (-15 + 3x)(2x + 3) = 0 Reorder the terms: (-15 + 3x)(3 + 2x) = 0 Multiply (-15 + 3x) * (3 + 2x) (-15(3 + 2x) + 3x * (3 + 2x)) = 0 ((3 * -15 + 2x * -15) + 3x * (3 + 2x)) = 0 ((-45 + -30x) + 3x * (3 + 2x)) = 0 (-45 + -30x + (3 * 3x + 2x * 3x)) = 0 (-45 + -30x + (9x + 6x2)) = 0 Combine like terms: -30x + 9x = -21x (-45 + -21x + 6x2) = 0 Solving -45 + -21x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-15 + -7x + 2x2) = 0 Factor a trinomial. 3((-3 + -2x)(5 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-3 + -2x)' equal to zero and attempt to solve: Simplifying -3 + -2x = 0 Solving -3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {-1.5, 5}
| y+(-14)=9 | | (3x-12)/(28-7x) | | 7x+4-x=3x-5 | | 13-x+16=25-3 | | -17-13x=41-15x | | -y+3=14 | | -199+6x=46-5x | | 3/5z=3/8 | | w/21=23/7 | | d^2+13d+12=0 | | y-(-8)=10 | | -x^2+75x-2=0 | | 5x-10x=9x+4 | | 7x^2-2+3x=0 | | 7y(18y-54)=71 | | t(t-5)-36=0 | | y=2x*2x-3 | | y=2x*2-3 | | (-5.5X10^3N/C^2xM^2)x?=?N/Mc^2xM^2 | | -2/3j/4 | | 1/2*x=0 | | 60z^5/15z^10 | | 8-3/4c=5 | | 2+3(3n+3)=38 | | 1-2*x=0 | | 36=-2x-3(-1+3x) | | 2sinx=9cosx | | 11-x+27=53-8 | | 5(b-73)=80 | | -114=-2(1+7b) | | 8y-4+y^2+31=180 | | -96=-3(7a-3) |